Microbiology - Black, Jacquelyn G. (John Wiley & Sons, 2013)
Jacquelyn Black's 8 th Edition of Microbiology: Principles and Explorations builds upon the previous best-selling textbooks in this series with an enhanced introduction to the study of Microbiology in the same engaging writing style throughout the narrative